Good Corporate Governance’s Role in Green Strategy, Innovation, and Carbon Disclosure - Acynthia Ayu Wilasittha; Evinda Dwi Nur Aini (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This research incorporating Good Corporate Governance (GCG) to investigates the connection between green strategy and green innovation in relation to carbon emission disclosure. The study adopts a quantitative methodology, utilising secondary data sourced from companies' sustainability reports and annual reports. Consumer non-cyclical companies listed on the IDX from 2021 to 2023 are the population. The samples are 44 companies were observed over a three-year period, utilising purposive sampling with defined criteria. The findings reveal that both green strategy and green innovation significantly influence carbon emission disclosure, indicating that companies effectively implementing the green strategy and green innovation practices tend to optimize their emission disclosures to enhance their reputation among stakeholders. Green strategy impacts on carbon emission disclosure is not moderated by GCG; however, GCG significantly moderates the correlation between disclosure and green innovation. This shows that certain consumer non-cyclical companies have not fully adopted GCG, thereby constraining the effectiveness of green strategies aimed at enhancing emission disclosure. Optimizing GCG implementation is therefore essential to reinforce both green strategy and green innovation, enabling companies to become more environmentally responsible and reduce operational carbon emissions, ultimately advancing corporate sustainability.